Between Nature and Culture: Lévi-Strauss’s Structural Analysis of Myth in the Light of Semiotics - Jankowska, Tatiana (Respectus Philologicus, 2014)
This article presents the influence of Claude Lévi-Strauss’s research in the field of cultural antropology on the guidelines and concepts of semiotics. Much empirical research in semiotics, connected with different systems of signs and revealing their functions in archaic human cultures, has been conducted on the ground of structural analysis. They are connected, among other things, with different cultures and societies, diversified both spatially and temporally. Thus, the integrating role of myth, as well as its uniting functions in the case of the organization of an individual consciousness, have a primeval modeling impact on the semiotic systems. According to Lévi-Strauss, there is a certain regularity of behaviors that stand for the mechanism of human symbolic communication. This regularity exists as an extention of the theory of signs that was previously worked out in the fields of structural linguistics and semiology. Lévi-Strauss’s theory concerns the collective unconscious of “the human mind” and is devoted to the unconscious nature of cultural phenomena, with a focus on searching for universal rules of thinking that are appropriate to all human minds. The subject of semiotics is a group of sign systems developed in different cultures. A cultural text presents a certain model of the world that we read using codes. The system of mythological signs reveals the cosmological concept of reality with relation to the mythopoetic view of the world.